Postprescription review improves in-hospital antibiotic use: A multicenter randomized controlled trial. (February 2015) - Lesprit, P.; de Pontfarcy, A.; Esposito-Farese, M.; Ferrand, H.; Mainardi, J.L.; Lafaurie, M.; Parize, P.; Rioux, C.; Tubach, F.; Lucet, J.C.
Abstract: Although review of antibiotic therapy is recommended to optimize antibiotic use, physicians do not always perform it. This trial aimed to evaluate the impact of a systematic postprescription review performed by antimicrobial stewardship program (ASP) infectious disease physicians (IDP) on the quality of in-hospital antibiotic use. A multicenter, prospective, randomized, parallel-group trial using the PROBE (Prospective Randomized Open-label Blinded Endpoint) methodology was conducted in eight surgical or medical wards of four hospitals. Two hundred forty-six patients receiving antibiotic therapy prescribed by ward physicians for less than 24 hours were randomized to receive either a systematic review by the ASP IDP at day 1 and days 3 to 4 (intervention group, n = 123) or no systematic review (usual care, n = 123). The primary outcome measure was appropriateness of antimicrobial therapy, a composite score of appropriateness of antibiotic use at days 3 to 4 and appropriate treatment duration, adjudicated by a blinded committee. Analyses were performed on an intention-to-treat basis. In the intervention group, appropriateness of antimicrobial therapy was more frequent (55/123, 44.7% vs. 35/123, 28.5%; odds ratio 2.03, 95% confidence interval 1.20–3.45). Antibiotic treatment duration was lower in the intervention group (median (interquartile range) 7 (3–9) days vs. 10 (7–12) days; p 0.003). ASP IDP counseling to change therapy was more frequent at days 3 to 4 than at day 1 (114/123; 92.7% vs. 24/123; 19.5%, p <0.001). Clinical outcome was similar between groups. This study suggests that a systematic postprescription antibiotic review performed at days 1 and 3 to 4 results in higher quality of antibiotic use and lower antibiotic duration. This trial was registered atClinicalTrials.gov (NCT01136200).